Neutrophil activation by immune complexes and the role of rheumatoid factor. Issue 1 (February 1984) - Gale, R; Bertouch, J V; Gordon, T P; Bradley, J; Roberts-Thomson, P J
Abstract : Membrane activation of human neutrophils by preformed immune complexes and heat aggregated human gammaglobulins was studied by chemiluminescence. Strong neutrophil activation was found with human-albumin rabbit-antialbumin complexes prepared at equivalence, with maximal activation occurring in slight antigen excess. Furthermore different preparations of heat aggregated gammaglobulin which were of large size also showed similar activity. In contrast, heat aggregates of small size were inactive and blocked the chemiluminescent response found with larger active aggregates. A purified monoclonal rheumatoid factor with specificity for IgG modulated these responses when preincubated with preformed complexes or aggregates. Both enhancement of the neutrophil chemiluminescence response with inactive preparations and suppression of the response with highly active preparations were observed. Kinetic studies of the neutrophil chemiluminescent response varied with respect to the activating preparation, but were generally biphasic. This observation suggested an initial direct membrane activation followed by a more delayed response reflecting phagocytosis of complexes. We have demonstrated the direct activation of neutrophil chemiluminescence by laboratory preparations of immune complexes. The chemiluminescent responses observed were influenced by both the size and immunochemical properties of the activating complexes and by the presence of rheumatoid factor. These observations may have important implications in the immunopathogenesis of immune-complex-mediated diseases.